2020
DOI: 10.1155/2020/6138409
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Carcinoma Presenting as Metastatic Disease to the Breast

Abstract: Medullary thyroid carcinoma (MTC) is a neuroendocrine tumor that is derived from C cells of the thyroid gland. It is a rare aggressive tumor, known to metastasize to lymph nodes, liver, bones, and lungs. A 41-year-old female, who presented with a breast mass, was initially diagnosed with invasive ductal carcinoma. She was also found to have a thyroid mass which was later diagnosed as MTC. On a rereview of the breast pathology, the morphologic features were strikingly similar to the MTC. Further investigation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Oncogenic RET activation stimulates cell proliferation and survival by triggering multiple intracellular signaling cascades. In an earlier study, Drosten et al characterized the downstream signaling pathways associated with RET required for tumor progression and maintenance in TT cells [ 55 , 56 , 57 , 58 ]. They disrupted RET phosphorylation and activation in TT cells by using an adenoviral vector expressing the truncated dominant-negative RET protein, which lacks the intracellular tyrosine kinase domain, leading to the suppression of the Raf/MEK/ERK and PI3K/Akt/mTOR pathways, implying their primary role in RET-mediated transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenic RET activation stimulates cell proliferation and survival by triggering multiple intracellular signaling cascades. In an earlier study, Drosten et al characterized the downstream signaling pathways associated with RET required for tumor progression and maintenance in TT cells [ 55 , 56 , 57 , 58 ]. They disrupted RET phosphorylation and activation in TT cells by using an adenoviral vector expressing the truncated dominant-negative RET protein, which lacks the intracellular tyrosine kinase domain, leading to the suppression of the Raf/MEK/ERK and PI3K/Akt/mTOR pathways, implying their primary role in RET-mediated transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Although MZ-CRC1, an MTC cell line with the M918T mutation, appears to be more resistant to adefovir dipivoxil treatment compared to TT cells carrying the C634W mutation ( Figure S1 ), it can be hypothesized that specific genes might be highly overexpressed in the RET M918T mutant but not in the C634W mutant. This overexpression could contribute to the increased resistance of MZ-CRC1 to the treatment [ 11 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Notably, we also found that normal thyroid cells, Nthy-ori-3-1, and hepatocytes cell lines showed significant resistance to adefovir dipivoxil, indicating that this compound is more selective for MTC.…”
Section: Discussionmentioning
confidence: 99%
“…Of all breast metastases only 4% originate from the thyroid. MTC breast metastasis is exceedingly rare with only 40 cases reported in the literature ( 4 , 5 ). The vast majority concerns women (only one male case reported); the mean age at diagnosis is 43.5 years ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…MTC breast metastasis is exceedingly rare with only 40 cases reported in the literature ( 4 , 5 ). The vast majority concerns women (only one male case reported); the mean age at diagnosis is 43.5 years ( 4 , 5 ). According to the literature, the time interval between the initial diagnosis and the breast metastasis varies from a few days or months to 28 years (mean 7.1 years) ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation